Second-look endoscopy and factors associated with delayed bleeding after endoscopic submucosal dissection - Kim, Su-Jin (World J Gastrointest Endosc, 2016)
Endoscopic submucosal dissection (ESD) is a widely used procedure as curative treatment for superficial gastric neoplasms, including early gastric cancer without lymph node metastasis. However, ESD requires advanced endoscopic skill and there is a major concern regarding complications from bleeding. So far, extensive efforts have been made to develop strategies to reduce post-ESD bleeding. Use of proton pump inhibitors and coagulating exposed vessels on the ulcer ﬂoor after ESD are strategies known to reduce the risk of delayed bleeding. Second-look endoscopy (SLE) is also carried out to reduce delayed bleeding following ESD in many institutions. However, the incidence of bleeding still remains around 5%, and further measures are needed to reduce delayed bleeding after gastric ESD. Recently, three randomized studies indicated that routine SLE was unnecessary. Although routine SLE may not be recommended for all patients after gastric ESD, SLE might be an important tool for the prevention of the delayed bleeding in selected high-risk patients. Thus, the identification of the risk factors, such as large size of resected specimen and treatment with multiple antiplatelet medications, may help to further guide clinicians in deciding whether to perform SLE. Studies carried out on larger cohorts are necessary to clarify the efficacy of SLE after ESD in the prevention of post-ESD bleeding in potentially high-risk patients.